KAJIAN PENGEMBANGAN BALAI LATIHAN KERJA ( BLK )KABUPATEN BREBES - Darwanto (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Brebes, 2018)
Unemployment in Indonesia is a classic problem that occurs in almost every region in Indonesia.Unemployment caused by several factors such as the lack of employment or lack of skills of thelabour force.Brebes has the unemployment rate averages – average of 8.25 percent in 2008 until2015. In addition, according to the Central Bureau of statistics the number of jobless in theBrebes Regency in 2015 achieving 53,261 inhabitants. Work Practice Hall is one of the solutionin addressing the problems of employment in Brebes Regency. This study aimed to find out thecondition of the existing Working Practice Hall in the Brebes Regency currently, as well asmaking policy and direction in the development of work in the Practice Hall Brebes Regency.The methods used in the research in the form of Content Analysis and SWOT (Strenght,Weakness, Opportunity, Threat). The results showed that the Work Practice Brebes RegencyHall is in the defensive. It means that to do development on the porch of a work practice needs todevelop the internal structure of Training Center in Brebes